Diversity ideologies in organizations - Thomas, Kecia M (Routledge, 2014)
Since the increased attention towards diversity in the workplace, the concepts of "diversity initiatives" and "diversity management" have become a common place in many conversations among academics and practitioners, alike. The diversity movement in the workplace originated from the increased avocation for equal treatment of minority groups due to the dynamic composition of the modern workforce. Many organizations were forced to face these changes and the dilemma of how to respond to group differences to maintain and/or increase organization effectiveness and productivity. This volume will present new research on the colorblindness versus multiculturalism debate, assist in broadening the diversity ideology conversation, share this conversation across social science domains including Industrial/Organizational Psychology, Social Psychology, and Law and Public Policy, and highlight how the nature of diversity ideology may be fluid and therefore be different depending on the diversity dimension discussed